14A+13B-6A+7=

Simple and best practice solution for 14A+13B-6A+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14A+13B-6A+7= equation:


Simplifying
14A + 13B + -6A + 7 = 0

Reorder the terms:
7 + 14A + -6A + 13B = 0

Combine like terms: 14A + -6A = 8A
7 + 8A + 13B = 0

Solving
7 + 8A + 13B = 0

Solving for variable 'A'.

Move all terms containing A to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + 8A + -7 + 13B = 0 + -7

Reorder the terms:
7 + -7 + 8A + 13B = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 8A + 13B = 0 + -7
8A + 13B = 0 + -7

Combine like terms: 0 + -7 = -7
8A + 13B = -7

Add '-13B' to each side of the equation.
8A + 13B + -13B = -7 + -13B

Combine like terms: 13B + -13B = 0
8A + 0 = -7 + -13B
8A = -7 + -13B

Divide each side by '8'.
A = -0.875 + -1.625B

Simplifying
A = -0.875 + -1.625B

See similar equations:

| 10=12-8 | | 4+4=-6 | | y=3-1/2x | | 5(a-1)-4(a-2)=2(5a+20) | | 10=2x-86 | | F(9)=3 | | 1000=r^3/2 | | 3(X+2X)+9R= | | 20y+3x=50 | | ((3y+4)*2)+((y+3)*2)=70 | | .5n+15=3n | | (X+5)(x+5)-49=0 | | -12=w+18 | | 5z-18-z+2= | | 10=(2*6)-8 | | 2x-3x-10=-9 | | B-2b=b+4b+2 | | 3(y-4)= | | 4x+8/4-2=x | | 2x^2-4x/x-2 | | 8+7x+4x=63 | | x+6=x.4 | | 99x+65=-4x | | z(4x^10y^11z^8)= | | 7+3C=-7 | | .25n=2n-21 | | 5(2x-12)+21=2x+21 | | w=4x(y-5) | | 210(-3)= | | 2(3+x)=20+3x | | 9y+2=11y+8 | | z(16xy^3z^3)= |

Equations solver categories